Ease of Governance -A Case of Pandemic - Agrawal, Sangita (RESEARCH REVIEW International Journal of Multidisciplinary, 2023)
The pandemic crisis has presented us with problems related to the availability of resources, provision of various services, and accountability of policy implementation. Governance was not only a requirement for the government but also the businesses and citizens. Covid-19 pandemic has changed how efficiency is maintained at multiple levels concerning the cost and the delivery of goods and services. Its effect and impact on the various social-economic statuses of the people was so severe and complex that it caused a lot of fear in society. These are evident through the economic activity paralysis, labor migration issues, hospital management issues, lack of health facility provisions, transportation issues, etc. This paper attempts to discuss a case study of ease of Governance during pandemic. This case study discussed the various governance issue required to build a capable system, in order to overcome the pandemic situation.